2004
DOI: 10.1089/089771504774129874
|View full text |Cite
|
Sign up to set email alerts
|

Intraventricular Infusion of the Neurotrophic Protein S100B Improves Cognitive Recovery after Fluid Percussion Injury in the Rat

Abstract: Elevated serum S100B levels have been shown to be a predictor of poor outcome after traumatic brain injury (TBI). Experimental data, on the other hand, demonstrate a neuroprotective and neurotrophic effect of this calcium-binding protein. The purpose of this study was to examine the role of increased S100B levels on functional outcome after TBI. Following lateral fluid percussion or sham injury in male Sprague Dawley rats (n = 56), we infused S100B (50 ng/h) or vehicle into the cerebrospinal fluid of the ipsil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 40 publications
1
29
0
2
Order By: Relevance
“…Neuroprotective effects of low concentrations of S100-beta are described in animal studies, resulting in improved learning and cognitive functioning through effects on neural plasticity and glial proliferation. 9,12,56 In parallel with these findings is the observation that ECT can give rise to sprouting and cell proliferation, particularly in serotonergic neurons in the hippocampal region. 57,58 Interestingly, higher baseline S100-beta concentrations in the neuroprotective range have been associated with better treatment response 50 and better cognitive functioning 59 in depressed patients.…”
Section: Resultsmentioning
confidence: 88%
“…Neuroprotective effects of low concentrations of S100-beta are described in animal studies, resulting in improved learning and cognitive functioning through effects on neural plasticity and glial proliferation. 9,12,56 In parallel with these findings is the observation that ECT can give rise to sprouting and cell proliferation, particularly in serotonergic neurons in the hippocampal region. 57,58 Interestingly, higher baseline S100-beta concentrations in the neuroprotective range have been associated with better treatment response 50 and better cognitive functioning 59 in depressed patients.…”
Section: Resultsmentioning
confidence: 88%
“…Animal experiments have demonstrated that intracerebral injection or infusion of S100 could improve cognitive recovery after traumatic brain injury [29] , facilitate memory processing in a dose-dependent way [30] and lead to the consolidation of passive avoidance memory [31] . Recently, histopathological studies demonstrated that mood disorders were characterized by disease-specific glial pathology [32,33] .…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Multiple experimental TBI models have shown significant increases in S100B levels in the brain early after TBI 28 and persisting up to 5 days. 29,30 Intraventricular infusion of S100B resulted in a significant improvement in memory function after lateral fluid percussion-induced brain injury, 29 but higher serum levels of S100B were correlated with impaired cognitive performance. The latter finding is in agreement with many clinical observations and was thought to reflect activation of secondary injury mechanisms.…”
Section: S100b Does Not Influence Key Microglial Activation Markers Imentioning
confidence: 99%